THE IMPACT OF ORAL HEALTH ON HUMAN SECURITY - Bulgan Battsengel,; Urjin Odkhuu,; Delgertsetseg Jargaltsogt, (International Journal of Innovative Technologies in Social Science, 2025)
To comply with the guidelines outlined in Article 3.4.1.1 of Mongolia's National Security Concept, which emphasizes "Human Security" and the promotion of public health, healthy lifestyles, and public health education, as well as Article 3.4.1.3, which focuses on proper nutrition, prevention of non-communicable diseases, and addressing micronutrient deficiencies, Mongolia has implemented two national programs aimed at oral health protection: the "Oral Health" program from 1999-2005 and 2006-2015, and the "Healthy Teeth - Healthy Children" program from 2019-2023. The World Health Organization (WHO) defines oral health as the overall well-being of the mouth, teeth, and gums, enabling individuals to perform essential functions like eating, breathing, and speaking. It also encompasses psychosocial aspects such as self-confidence and overall psychological well-being. Oral health is essential across all stages of life, from childhood to old age, and plays a crucial role in overall health, enabling individuals to fully engage in society and reach their potential. Oral diseases are largely preventable but pose a significant health burden in many countries, leading to illness, discomfort, and even mortality. These diseases share modifiable risk factors with other non-communicable diseases (NCDs), including sugar consumption, tobacco use, alcohol consumption, and poor hygiene, influenced by social and commercial factors. Common oral diseases include dental caries, periodontal disease, oral cancer, oral trauma, and cleft lip and palate, affecting approximately 3.5 billion people worldwide regardless of age or gender. Addressing oral hygiene at a systemic level is crucial, with developing countries facing higher prevalence due to factors like low household income, lack of oral hygiene knowledge, and inadequate national policies for prevention. Socio-economic disparities in oral health are pronounced among disadvantaged populations. The 2017 Mongolian National Oral Health Survey revealed high prevalence and severity of dental caries across different age groups, highlighting the need for comprehensive research in this area. Tooth decay can lead to infections in other organs, such as tonsillitis, cardiovascular disease, joint disease, kidney disease, diabetes, and allergies. It is considered both a lifestyle-related disease influenced by dental care and nutrition, as well as an infectious source that can be transmitted from an infected individual to a healthy person.